National cyber emergencies the return to civil defence - Austin, Greg 1951- (Routledge studies in conflict, security and technology, 2020)
"This book documents and explains civil defence preparations for national cyber emergencies in conditions of both peace and war. The volume analyses the escalating sense of crisis around state-sponsored cyber-attacks that have emerged since 2015, when the United States first declared a national emergency in cyber space. It documents a shift in thinking in the USA, from cooperative resilience-oriented approaches at national level to more highly regulated, state-led civil defence initiatives. Although the American response has been mirrored in other countries, the shift is far from universal. Civil defence strategies have come into play but the global experience of that has not been consistent or even that successful. Containing contributions from well-placed scholars and practitioners, this volume reviews a selection of national experiences (from the USA, India, China, Estonia, and Finland) and a number of key thematic issues (information weapons, alliance coordination, and attack simulations). These demonstrate a disconnect between the deepening sense of vulnerability and the availability of viable solutions at the national level. Awareness of this gap may ultimately lead to more internationally oriented cooperation, but the trend for now appears to be more conflictual and rooted in a growing sense of insecurity. This book will be of much interest to students of cyber-security, homeland security, disaster management and International Relations, as well as practitioner and policy-makers"--